(NmINERALY I METODY IH ISSLEDOWANIQ (B:s (NmEVWUZOWSKIJ SBORNIK NAU^NYH TRUDOW (B/s - (NpORO[INA(B, (Nn(B.(Na(B.s ((NnOWOSIBIRSK (B:s (NiZD(B-(NWO nOWOSIBIRSK(B. (NPED(B. (NIN(B-(NTA(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NnOWOSIB(B. (NGOS(B. (NPED(B. (NIN(B-(NTs
Keywords: (NmINERALOGI^ESKIE ISSLEDOWANIQs